Immunotherapeutic Potential of the Yellow Fever Virus Vaccine Strain 17D for Intratumoral Therapy in a Murine Model of Pancreatic Cancer - Alina S. Nazarenko; Yulia K. Biryukova; Kirill N. Trachuk; Ekaterina A. Orlova; Mikhail F. Vorovitch; Nikolay B. Pestov; Nick A. Barlev; Anna I. Levaniuk; Ilya V. Gordeychuk; Alexander S. Lunin; Grigory A. Demyashkin; Petr V. Shegai; et al. (Vaccines)
Objective: We evaluate the immunotherapeutic potential of the yellow fever virus vaccine strain 17D (YFV 17D) for intratumoral therapy of pancreatic cancer in mice. Methods: The cytopathic effect of YFV 17D on mouse syngeneic pancreatic cancers cells were studied both in vitro and in vivo and on human pancreatic cancers cells in vitro. Results: YFV 17D demonstrated a strong cytopathic effect against human cancer cells in vitro. Although YFV 17D did not exhibit a lytic effect against Pan02 mouse cells in vitro, a single intratumoral administration of 17D caused a delay in tumor growth and an increase in median survival by 30%. Multiple injections of 17D did not further improve the effect on tumor growth; however, it notably extended the median survival. Furthermore, preliminary immunization with 17D enhanced its oncotherapeutic effect. Conclusions: Intratumoral administration of yellow fever virus vaccine strain 17D delayed tumor in a murine model of pancreatic cancer. The fact that YFV 17D in vitro affected human cancer cells much more strongly than mouse cancer cells appears promising. Hence, we anticipate that the in vivo efficacy of YFV-17D-based oncolytic therapy will also be higher against human pancreatic carcinomas compared to its effect on the mouse pancreatic tumor.